Microstructural Changes of High Strength Concrete during Low Cycle Compression Fatigue Test after Exposure to High Temperature - Zhao, Dongfu; He, Wenbo; Hao, Peiyuan (Periodica Polytechnica Civil Engineering, 2023)
Using ultrasonic detection, microhardness test, scanning electron microscope test, mercury intrusion method and X-ray diffraction, the parameters of sonic time, microhardness, pore size distribution, cumulative pumping of high strength concrete under low cycle compression loading are tested after exposure to 200 °C, 400 °C and 600 °C. Experimental study showed that with the increasing loading times, the rangeability of sonic time, the microhardness, and total pore volume shows an overall trend of fast-slow-fast. Furthermore, the sonic time and microhardness are linearly related to the longitudinal fatigue strain. The research results provided references for nondestructive testing, fatigue damage analysis and structural evaluation of concrete structures subjected to fire or other high temperature processes.